PERSONALITY: HOW DOES IT IMPACT TEACHERS’ ORGANIZATIONAL COMMITMENT? - Purwani Puji Utami; Alexius Dwi Widiatna; Syamzah Ayuningrum; Arbiana Putri; Herlyna Herlyna; Adisel Adisel (LPMPP Universitas Negeri Yogyakarta, 2021)
Teacher organizational commitment is a determining factor for achieving quality education. It is believed that teacher personality is one of the main factors which either increase or decrease organizational commitment. This research aims to examine the effects of teacher personality on their organizational commitment. The quantitative approach was employed with the survey method. The samples were selected using the simple random technique by applying the Slovin formula. The participants of this study were 83 civil servant teachers at public senior high schools located in East Jakarta. The data of this study were collected through a survey and then analyzed using Path analysis. The results of the analysis show that tcount is higher than ttable (4.329 2.64). This result means that H0 is rejected while H1 is accepted. The hypothesis testing shows that personality has a positive direct effect on teacher organizational commitment. Furthermore, it is proven that there are three traits influencing teacher personality, namely emotional stability (33.98%), extroversion (33.56%), and openness to experience (32.46%). Meanwhile, the main factors influencing organizational commitment are employee engagement (33.74%), moral responsibility (33.55%), and loyalty (32.71%). Based on the result of this study, it is suggested that school principals take teacher personality into account in order to improve teacher organizational commitment at schools.